Endosomal trafficking and related genetic underpinnings as a hub in Alzheimer's disease. Issue 10 (22nd August 2022) - Limone, Adriana; Veneruso, Iolanda; D'Argenio, Valeria; Sarnataro, Daniela
Abstract: Genetic studies support the amyloid cascade as the leading hypothesis for the pathogenesis of Alzheimer's disease (AD). Although significant efforts have been made in untangling the amyloid and other pathological events in AD, ongoing interventions for AD have not been revealed efficacious for slowing down disease progression. Recent advances in the field of genetics have shed light on the etiology of AD, identifying numerous risk genes associated with late‐onset AD, including genes related to intracellular endosomal trafficking. Some of the bases for the development of AD may be explained by the recently emerging AD genetic "hubs, " which include the processing pathway of amyloid precursor protein and the endocytic pathway. The endosomal genetic hub may represent a common pathway through which many pathological effects can be mediated and novel, alternative biological targets could be identified for therapeutic interventions. The aim of this review is to focus on the genetic and biological aspects of the endosomal compartments related to AD progression. We report recent studies which describe how changes in endosomal genetics impact on functional events, such as the amyloidogenic and non‐amyloidogenic processing, degradative pathways, and the importance of receptors related to endocytic trafficking, including the 37/67 kDa laminin‐1 receptor ribosomal protein SA, and their implications for neurodegenerative diseases.